The Impact of Emigration on Source Country Wages : Evidence from the Republic of Moldova - Bouton, Lawrence; Paul, Saumik; Tiongson, Erwin R. (2012)
Thousands of Moldovans emigrated for work abroad over the last few years following nearly a decade of economic stagnation in their home country. At about 30 percent of the labor force, Moldova's emigrant population is in relative terms among the largest in the world. This study uses a unique household survey to examine the impact of emigration on wages in Moldova. The authors find a positive and significant impact of emigration on wages and the result is robust to the use of alternative samples and specifications. The size of the emigration coefficient varies depending on the sample and model specification, but the baseline result suggests that, on average, a 10 percent increase in the emigration rate is associated with 3.2 percent increase in wages. At the same time, there is evidence of significant differences across economic sectors in the estimated effect of emigration on wages. The authors speculate and provide some evidence that offsetting changes in labor demand, as revealed by information on employment growth by sector, may help explain some of the heterogeneity.